Nutrient Level of a Young Tropical Hydroelectric Dam Reservoir in Sarawak, Malaysia - Ling, Teck Yee; Gerunsin, Norliza; Soo, Chen Lin; Lee, Nyanti; Sim, Siong Fong; Grinang, Jongkar (Borneo Journal of Resource Science and Technology, 2018)
Monitoring the nutrient level of a reservoir is crucial as excess nutrients can lead to hypoxia and fish kills in the reservoir. Hence, this study was carried out to examine the nutrient level of the Bakun reservoir, which is a newly built hydroelectric reservoir in Sarawak, Malaysia. Water samples were taken at five stations in the reservoir at three different depths (surface layer, 10 m, and 20 m) in November 2013. The present study demonstrated that Bakun reservoir contained low nitrite-nitrogen (≈ 0.005 mg/L) and nitrate-nitrogen (≈ 0.005 mg/L) concentrations but high five-day biochemical oxygen demand (≈ 4.73 mg/L) and organic Kjeldahl nitrogen (≈ 0.16 mg/L) concentrations indicating that organic pollution occurred in the reservoir. On the other hand, a mean total phosphorus concentration of 98.3 μg/L in the Bakun reservoir complied with the 200 μg/L standard value of Class II according to National Water Quality Standards in Malaysia. The nutrient level in the Bakun reservoir differed according to sampling stations and depths. Samplings stations located at Murum River downstream of the Murum dam construction site showed peak value of turbidity (182 FNU) and organic Kjeldahl nitrogen (0.45 mg/L) particularly at deeper water column. Batang Balui and Linau River were observed with higher five-day biochemical oxygen demand (> 6 mg/L) compared to other stations. Station near to the Bakun hydroelectric dam contained relatively high nitrite-nitrogen and total phosphorus concentrations but low nitrate-nitrogen and organic Kjeldahl nitrogen concentrations. Anthropogenic activities such as floating house and Murum dam construction have influenced the nutrients level in the reservoir. Keywords : Bakun hydroelectric reservoir, dam construction, nitrogen, phosphorus, turbidity